2023
DOI: 10.3390/plants12030524
|View full text |Cite
|
Sign up to set email alerts
|

Co-Inoculation of Endophytes Bacillus siamensis TUR07-02b and Priestia megaterium SMBH14-02 Promotes Growth in Rice with Low Doses of Nitrogen Fertilizer

Abstract: Multiple biotic and abiotic factors influence rice cultivation. These factors limit productivity and yield, as well as an irrational use of agrochemicals in rice cultivation. A sustainable alternative is using selected growth-promoting microorganisms to increase nutritional efficiency. In the present study, the direct mechanisms of growth promotion in two strains of Bacillus, three strains of Priestia, and two strains of Burkholderia endophytes of rice were characterized. Bacillus siamensis TUR07-02b and Pries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 83 publications
1
2
0
Order By: Relevance
“…Our search showed that the soilless observed trends in overall yield growth were similar to those reported in studies that employed PGPM in soil-based cropping systems; AMF inoculation in hydroponics, under reduced nutrient levels, increased the total yield by 49.54%, which is consistent with results obtained in soil cultivations (46-50% increase) [85]. In addition, endophytes were shown to increase total yield by 22.12%, just as demonstrated under limited-N soil conditions (31-39% increase) [86].…”
Section: Concluding Remarks and Future Implicationssupporting
confidence: 86%
“…Our search showed that the soilless observed trends in overall yield growth were similar to those reported in studies that employed PGPM in soil-based cropping systems; AMF inoculation in hydroponics, under reduced nutrient levels, increased the total yield by 49.54%, which is consistent with results obtained in soil cultivations (46-50% increase) [85]. In addition, endophytes were shown to increase total yield by 22.12%, just as demonstrated under limited-N soil conditions (31-39% increase) [86].…”
Section: Concluding Remarks and Future Implicationssupporting
confidence: 86%
“…subtilis and P. megaterium have been reported to be closely associated with plant microbial communities and to have plant-growth and disease-suppressing properties. Comparison of the GH32-encoding genes in publicly available genomes of both species reveals a special set of intracellular enzymes in P. megaterium of which only one homologue is present in B.…”
Section: Introductionmentioning
confidence: 99%
“…Rhizospheric bacteria play a fundamental role in plant health and productivity through establishing close symbiotic relationships with plant roots, specifically in the zone known as the rhizosphere. This beneficial relationship influences multiple aspects of plant growth, such as nitrogen fixation, nutrient solubilization, the production of indole acetic acid and siderophores, and protection against pathogens [ 1 , 2 ]. Additionally, cover crop legumes represent a valuable tool for promoting sustainable agricultural practices, providing multiple benefits for soil health, biodiversity, and agricultural productivity [ 3 ].…”
Section: Introductionmentioning
confidence: 99%